2000
DOI: 10.1295/polymj.32.57
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Poly(enaminonitrile)s

Abstract: Poly(enaminonitrile)s (PEANs), a new class of thermally stable aromatic polymers, possess excellent thermal stability, good mechanical properties and are easily soluble in many organic solvents. Flexible, tough films can be cast from these solutions. These polymers undergo a 'curing' reaction at 300--350°C to insoluble, more dimensionally stable materials without evolution of volatile byproducts. We summarize here the dielectric data measured at a frequency of 100 kHz, 25°C for some PEANs, and discuss the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…The short crystallization times typical of electrospinning lead to the assumption that the crystallites have a tendency to be small and to contain defects; furthermore, the degree of crystallization may be reduced. [303] In the case of PLA, it was observed that the degree of crystallinity and the melting point of the electrospun fibers were very similar to those of macroscopic samples. For instance, in the cases of nanofibers of PET, poly(ethylene naphthalate), and mixtures of the two, the melting points are not changed by the processing into nanofibers.…”
Section: Nanofiber Morphologiesmentioning
confidence: 87%
See 1 more Smart Citation
“…The short crystallization times typical of electrospinning lead to the assumption that the crystallites have a tendency to be small and to contain defects; furthermore, the degree of crystallization may be reduced. [303] In the case of PLA, it was observed that the degree of crystallinity and the melting point of the electrospun fibers were very similar to those of macroscopic samples. For instance, in the cases of nanofibers of PET, poly(ethylene naphthalate), and mixtures of the two, the melting points are not changed by the processing into nanofibers.…”
Section: Nanofiber Morphologiesmentioning
confidence: 87%
“…[303] Blend fibers are generally fabricated by electrospinning ternary solutions of two polymers and a solvent. To be able to interpret the properties of the fibers produced by melt electrospinning, it is necessary to determine whether the blend components have undergone a chemical reaction, either during blending or during the electrospinning process.…”
Section: Melt-electrospun Polymersmentioning
confidence: 99%
“…These characteristics are essential for various practical applications such as separation membranes, wound dressing materials, artificial blood vessels, sensors, composite reinforcements, and so forth. [1][2][3][4][5] In electrospinning, polymer solution or melt is placed in a container that has a millimeter size capillary.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim et al investigated the dynamic mechanical properties of poly(styrene-co-itaconate) 9 and poly(styrene-co-citraconate) 10 ionomers, both of which have two ion pairs in one ionic repeat unit. They found that the two ionomer systems show only very weak clustering and suggested that the polymer chains, where ionic groups are attached, experience steric hindrance when the ionic groups form multiplets and, thus, form only a few multiplets, leading to weak clustering.…”
Section: Introductionmentioning
confidence: 99%